Anda di halaman 1dari 18

1

INVERSE TRIGONOMETIC

INVERSE TRIGONOMETRIC FUNCTIONS


2.1.

INTRODUCTION
We have read about functions, one-one onto (bijective) functions and inverse of a function. We have
also learnt that inverse of a function f is denoted by f1 and f1 exists if and only if f is a one-one onto
function. There are several functions which are not one-one onto and hence their inverse does not exist.
We have also read about trigonometric functions are not one-one onto over their natural domains and
ranges and hence their, inverse do not exist. But if we restrict their domains and ranges, then they
will become one-one onto functions and their inverse will exist. In this chapter we will study inverses
of trigomometric functions and their various properties.

2.2.

INVERSE OF A FUNCTION
Let f : A B If (be a function from A to B) which is one-one onto. Then a function f1 : B A (f1 from
B to A) is said to be the inverse of the function f if
y = f(x) f1(y) = x
i.e., image of x under f is y image of y under f1 is x.
Clearly domain f1 = range f and

range f1 = domain f

2.3.

PRINCIPAL BRANCHES OF INVERSE TRIGONOMETRIC FUNCTIONS

(i)

Definition of sin1 x (Principal branch of sin1 x) :


p p

p p

sin1 : [1, 1] - , i.e., sin1 is a function from [1, 1] to - 2 , 2 .

2 2

(ii)

Such that

sin1 x = q x = sin q

where

1 x 1 and

p
2

q<

p
2

Definition of cos1 x (Principal branch of cos1 x) :


cos1 : [1, 1] [0, p] is such that cos1 x = q x = cos q,
where 1 x 1 and 0 q p

(iii)

Definition of tan1 x (Principal branch of tan1 x) :

p p

tan1 : (, ) - 2 , 2 such that

tan1 x = q x = tan q
where < x < and

p
2

<q<

p
.
2

www.thinkiit.in

2
(iv)

INVERSE TRIGONOMETIC
Definition of cot1 x : cot1 : (, ) (0, p) such that
cot1 x = q x = cot q, where < x < and 0 < q < p.

(v)

Definition of sec1 x : sec1 : (, 1] [1, ) [0, p] 2 such that



sec1 x = q x = sec q
where, < x 1 or 1 x < and 0 q <

(vi)

p
2

or

p
2

<qp

Definition of cosec1 x :
p p

cosec1 : (, 1] [1, ) - , {0}


2 2

such that cosec1 x = q x = cosec q


where < x 1 or 1 x < and

p
2

q < 0 or 0 < q

p
2

Summary
Function

Domain of the function

Principal value branch


p
2

p
2

1.

y = sin1x

1 x 1

2.

y = cos1 x

1 x 1

0yp

3.

y = tan1 x

< x <

4.

y = cot1 x

< x <

0<y<p

5.

y = sec1 x

x 1 or x 1

0 y p, y

6.

y = cosec1 x

x 1 or x 1

p
2

p
2

<y<

p
2

p
2

p
,y0
2

Note : Unless otherwise stated sin1 x, cos1 x, tan1 x, cot1, x sec1 x and cosec1 x will mean their
principal branches.
2.4

GRAPHS OF PRINCIPAL BRANCHES OF INVERSE TRIGONOMETRIC FUNCTIONS


Y
y=1

(i)

Graph of y = sin x
Domain = R = ( , )
and Range = [1, 1]

- 2p

3p
2

p
2

p
2

y = 1

www.thinkiit.in

3p
2

2p

INVERSE TRIGONOMETIC
Graph of y = sin x
1

Domain = [1, 1]

p
2

p p

Range = - 2 , 2

(ii)

p
2

Graph of y = cos x

y=1

Domain = R = (, )
Range = [1, 1]

3p
2

p
2

O p
2

3p
2

y = 1
Y

Graph of y = cos1 x

Domain = [1, 1]

p
2

Range = [0, p]
O

(iii)

Graph of y = tan x

Domain = R x : x = (2n + 1) , n Z
2

Range = (, )

p
2

p
2

Y
p
y=
2

Graph of y = tan1 x
Domain = R = (, )
Range =

p
4

p p
- ,
2 2

O
-p
4
y=

-p
2

(iv)

Graph of y = cot x
Domain = R {x : x = n p, n Z}
Range = (, )

p
2

O p
2

www.thinkiit.in

INVERSE TRIGONOMETIC
Y

Graph of y = cot x
1

Domain = (, )

3p
2

Range = (0, p)

p
2

p
4
O

(v)

Graph of y = sec x
p
2

Domain = R x : x = (2n + 1) , n Z

Range = (, -1] [1, )

p
2

p
2

Graph of y = sec1 x

Domain = (, -1] [1, )

Range = 0, 2 2 , p = [0, p] 2

p
2
1

(vi)

3p
2

Graph of y = cosec x

Domain = R {x : x = n p, n Z}
Range = (, 1] [1, )

p
2
O

p
2

Graph of y = cosec1 x

Domain = (, -1] [1, )


p

p/2

p p

Range = - 2 , 0 0, 2 = - 2 , 2 {0}

- p/2

2.5.

SOME IMPORTANT PROPERTIES OF INVERSE TRIGONOMETRIC FUNCTIONS


Property I :
(i)
sin (sin1 x) = x for all x [1, 1]
(ii)
cos (cos1 x) = x,
for r all x [1, 1]
1
(iii)
tan (tan x) = x,
for all x R
1
(iv)
cot (cot x) = x,
for all x R.
1
(v)
sec (sec x) = x,
for all x ( , 1] [1, ) i.e., for all x 1 or x 1
(vi)
cosec (cosec1 x) = x, for all x (, 1] [1, ) i.e., for all x 1 or x 1

www.thinkiit.in

INVERSE TRIGONOMETIC
Property II :
p p

(i)

sin1 (sin x) = x, x - 2 , 2

(iii)

tan1 (tan x) = x, x - 2 , 2

(v)

sec1 (sec x) = x, x 0, 2 2 , p i.e., x (0, p)

(vi)

cosec1 (cosec x) = x, x - 2 , 0 0, 2 i.e., x - 2 , 2 {0}

p p

sin1 (sin x) =

cos1 (cos x) =

tan1 (tan x) =

cos1 (cos x) = x, x [0, p]

(iv)

cot1 (cot x) = x, x (0, p)

- p - x

x,

p-x

x - 2p

3p - x,

(ii)

p

2

p p

p
3p
x2
2
p
p
- x
2
2
p
3p
x
2
2
3p
5p
x
2
2
7p
5p
x
and so on
2
2
-

if
if
if
if
if

- x,
x,

2p - x,
x - 2p,
4p - x,

-px0
0xp
p x 2p
2p x 3p
3p x 4p and so on

p
3p
<x<2
2
p
p
- <x<
2
2
p
3p
<x<
2
2
5p
3p
and so on
<x<
2
2

x + p,

x,

x - p,

x - 2p,

Property III :
(i)

sin1 x = cosec1
cosec1 x = sin1

(ii)

cos1x = sec1
sec1 x = cos1

1
, 1 x 1 and x 0
x
1
, x 1 or x 1
x

1
, 1 x 1
x
1
, x 1 or x 1
x

(iii)

tan1x = cot1 x , x > 0 = p + cot1 x , x < 0



(iv)

cot1 x = tan1 x , x > 0 = p + tan1 x , x < 0



www.thinkiit.in

INVERSE TRIGONOMETIC
Property IV :
(i)
sin1 ( x) = sin1 (x),
(ii)
cos1 ( x) = p cos1 x,
(iii)
tan1 ( x) = tan1 x,
(iv)
cot1 ( x) = p cot1 x,
(v)
sec1 ( x) = p sec1 x,
(vi)
cosec1 ( x) = cosec1 x,

for all x [1, 1]


for all x [1, 1]
for all x R
for all x R
for all x (, 1] [1, ) i.e., for all |x| 1
for all x (, 1] [1, ] i.e., for all |x| 1

Property V :
p
,
2

(i)

sin1 x + cos1 x =

(ii)

tan1x + cot1 x =

(iii)

sec1 x + cosec1 x =

for all x [1, 1]

p
,
2

for all x R
p
2

for all x (, 1] [1, ) i.e., for all |x| 1

Property VI :

(i)

tan1 x + tan1 y =

x+y
,
tan -1

1 - xy

-1 x + y
,
p + tan
1 - xy

-1 x + y
,
- p + tan

1 - xy

if xy < 1
if x > 0, y > 0 and xy > 1
if x < 0, y < 0 and xy > 1

Property VII :
x-y

tan1 x tan1 y = tan1 1 + xy , if xy > 1


This result can be established by putting y in place of y in the results of property V using the
fact that tan 1 ( y) = tan1 y.

tan1 x tan1 y =

x-y
,
tan -1

1 + xy

-1 x - y
,
p + tan
1 + xy

-1 x - y
,
- p + tan

1 + xy

if xy > -1
if x > 0, y < 0 and xy < -1
if x < 0, y > 0 and xy < -1

Property VIII :

sin1 x + sin1 y =

sin -1{ x 1 - y 2 + y 1 - x 2 } ,

p - sin -1 { x 1 - y 2 + y 1 - x 2 } ,

-1
2
2
- p - sin { x 1 - y + y 1 - x } ,

if - 1 x, y 1 and x 2 + y 2 1
or if xy < 0 and x 2 + y 2 > 1
if 0 < x, y 1 and x 2 + y 2 > 1
if - 1 x, y < 0 and x 2 + y 2 > 1

www.thinkiit.in

INVERSE TRIGONOMETIC
Property IX :

sin1 x sin1 y =

-1
2
2
sin { x 1 - y - y 1 - x } ,

-1
2
2
p - sin { x 1 - y - y 1 - x } ,

-1
2
2
- p - sin { x 1 - y - y 1 - x } ,

if - 1 x, y 1 and x 2 + y 2 1
or if xy < 0 and x 2 + y 2 > 1
if 0 < x 1, - 1 y 0 and x 2 + y 2 > 1
if - 1 x < 0, 0 < y 1 and x 2 + y 2 > 1

Property X :

cos1 x + cos1 y =

2
2
-1
if - 1 x, y 1 and x + y 0
cos xy - 1 - x 1 - y ,

2p - cos -1 xy - 1 - x 2 1 - y 2 , if - 1 x, y 1 and x + y 0

Property XI :
cos -1 { xy + 1 - x 2 1 - y 2 } ,

cos1 x cos1 y =

- cos -1 { xy + 1 - x 2

if - 1 x, y 1 and x y

1 - y 2 } , if - 1 y 0, 0 < x 1 and x y

This result can be established in the same way as in property X.


Property XII :

(i)

2 tan1 x =

2x
tan -1

, if - 1 < x < 1
1 - x2

-1 2x
, if x > 1
p + tan
1 - x2

-1 2x
- p + tan
, if x < -1
1- x2

Property XIII :

(i)

(ii)

2 tan1 x =

2x
sin -1
, if - 1 x 1

1+ x2

-1 2x
, if x > 1
p - sin
1+ x2

-1 2x
, if x < -1
- p - sin
1+ x 2

2 tan1 x =

1 - x2
, if 0 x <
cos -1
1 + x2

-1 1 - x
, if - < x 0
- cos
2
1+ x

www.thinkiit.in

INVERSE TRIGONOMETIC
Property XIV :

(i)

sin1 x = cos1 1- x 2 = tan1


1 - x2

2
1
x

= cot1 1 - x = sec1

Where x 0
(ii)

2
1- x
x

cos1 x = sin1 1- x 2 = tan1

1
= cot1
= cosec1
2 = sec
2
x
1- x
1- x

Where x > 0

(iii)

1

x

1
tan1 x = sin1
2 = cos
2
1+ x
1+ x

= cot

= sec

1+ x

= cosec

2
1+ x

Property XV :

(i)

2 sin x =
1

-1
1
2
x
if sin ( 2x 1 - x ),
2

-1
2
x 1
p - sin (2x 1 - x ), if
2

2
- p - sin (2x 1 - x ), if - 1 x

1
2
1
2

Property XVI :
(i)

cos -1(2x 2 - 1) ,
if 0 x 1
2p - cos -1(2x 2 - 1) , if - 1 x 0

2 cos1 x =

Property XVII :

3 sin1 x =

sin -1(3 x - 4 x 3 ) ,

-1
3
p - sin (3x - 4x ) ,

- p - sin -1(3 x - 4 x 3 ) ,

if if

1
1
x
2
2

1
x 1
2

if - 1 x -

= cosec1 x

1
2

www.thinkiit.in

INVERSE TRIGONOMETIC
Property XVIII :

3 cos1 x =

-1
3
if x 1
cos ( 4x - 3 x ) ,
2

1
1
-1
3
2p - cos ( 4 x - 3x ) , if - x
2
2

2p + cos -1( 4 x 3 - 3x ) , if - 1 x - 1

Property XIX :

3 tan1 x =

3 x - x3
,

tan-1
1 - 3x 2

-1 3 x - x
,
p + tan
2

1 - 3x

- p + tan-1 3x - x ,
1 - 3x2

if -

if x >

<x<

1
3

if x < -

3
1
3

www.thinkiit.in

10

INVERSE TRIGONOMETIC

SOLVED PROBLESM
Ex.1

Write each of the folloiwng functions in the simplest form :

2
2 , | x | < a
a
x

(i) tan1
Sol.

(i)

3a2x - x3
-a

3
x
2 , a > 0;
a
3
ax
3

tan

2
2
a -x

Thus, tan

= tan

2
2
a -x

a sin q

2
2
2
a - a sin q

tan

a sin q

= sin1 a

3a 2 x - x 3

a3 - 3ax 2

= tan

3a3 tan q - a3 tan3 q

a3 - 3a3 tan2 q

= tan

3 tan q - tan3 q

1 - 3 tan2 q

= tan1 (tan 3q) = 3q = 3 tan1 a



3a3 x - x 3
x

1
Thus, tan1 3
2 = 3 tan
a

a - 3ax

Sol.

Simplify :
a cosx - b sinx
a
, if
tan x > 1
b
cos
x
+
a
sin
x
b

(i)

tan1

(ii)

tan

(i)

We have

tan

1
2

2x
1 - y2
sin -1
,| x | < 1, y > 0 and xy < 1
+ cos -1
2

1+ x
1 + y 2

a cos x - b sin x

b cos x + a sin x

= tan

a cos x - b sin x

b cos x

b cos x + a sin x

b cos x

= tan

a
- tan x

b
1 + a tan x

p-q
a
= tan1 1 + pq , where p = and q = tan x
b

= tan1 p tan1 q = tan1 b tan1 (tan x) = tan1 b x




(ii)

= tan1 a cos q = tan1 (tan q) = q = sin1 a

Let x = a tan q. Then


1

Ex.2

Let x = a sin q. Then,


1

(ii)

(ii) tan

Let x = tan q and y = tan f. Then


tan

1 sin -1 2x + cos -1 1 - y
2
1+ x
1 + y 2
2

www.thinkiit.in

11

INVERSE TRIGONOMETIC
1 -1 2x
1 - y 2
1
sin
+ cos -1
2
1 + y 2
1+ x2 2

= tan

-1
-1
= tan 2 (2 tan x ) + 2 [2 tan ( y)]

tan q + tan f

x+y

= tan (tan1 x + tan1 y) = tan (q + f) = 1 - tan q tan f = 1 - xy


Ex.3

Prove that
(i) tan1

Sol.

(i)

2
11

+ tan1

= tan1

2
11

+ tan

tan

tan

1
2

7
24

= tan

1
7

1
2

+ tan1

+ tan

Now, 2 tan1

= tan1

1
2

+ tan1

1
2

+ tan1

1
7

= tan1

31
17

7
2
+

11
24

1- 2 7

11 24

125
1
= tan1 250 = tan1
2

= tan

9
13

1
7

1 1
+

2 7
1- 1 1

2 7

= tan1

= tan1

1
2

= tan1 13

..............(1)
1

-1
-1
+ tan 2 + tan 7

1 9
+

2 13
1- 1 9

2 13

31

= tan1 17

Find the value of :

2p

(i) sin1 sin 3


Sol.

(ii) 2 tan1

We have
1

Ex.4

1
2

We have
1

(ii)

7
24

(i)

(ii) tan1 tan

3p

(iii)

We know that sin1 (sin x) = x


2p

2p
sin1 sin 3 =

But,

2p
3

However,

p p

- 2 , 2 , which is the principal branch of sin1 x

2p
p p
2p

p
p
sin 3 = sin p - 3 = sin and - 2 , 2

3
3
2p

p
Hence, sin1 sin 3 =

(ii)

We know that tan1 (tan x) = x


3p

3p
tan1 tan 4 =

But,

3p
4

p p

- 2 , 2 , which is the principal branch of tan1 x

www.thinkiit.in

cos1 cos

7p

12

INVERSE TRIGONOMETIC
However,

tan

p p

p
= tan p + - = tan - 4 and - 4 - 2 , 2

3p
4

3p

p
Hence, tan1 tan 4 =

(iii)

We know that cos1 (cos x) = x


7p

7p
cos1 cos 6 =

But,

7p
6

[0, p] which is the principal branch of cos1 x


5p

5p
5p
= cos 2p - 6 = cos
and
(0, p)

6
6

7p
6

However, cos

7p

5p
Hence, cos1 cos 6 =

Ex.5

Prove that
1+ x - 1- x
1
p
1
tan1 1 + x + 1 - x = cos1 x, for
x1
2
2
2

Sol.

Let x = cos 2 q. Then,

1+ x

= 1 + cos 2q = 2 cos2 q = 2 cos q

= 1 - cos 2q = 2 sin2 q = 2 sin q

and

1- x

1+ x - 1 - x
LHS = tan1 1 + x + 1 - x

2 cos q - 2 sin q
= tan1 2 cos q + 2 sin q = tan1

cos q - sin q

cos q + sin q

1 - tan q

= tan 1 1 + tan q = tan 1

tan - q

4
p
4

=
Ex.6

q=

1
2

cos1 (x) = RHS

1- x
1
cos1 1+ x ,
2

x (0, 1)

Let x = tan2 q. Then,

Further, RHS =
Ex.7

Prove that
tan1 x =

Sol.

p
4

= tan q; and so tan1 ( x ) = tan1 (tan q) = q

1
2

cos

1- x

1+ x

1
2

cos

1 - tan 2 q

1 + tan 2 q

1
2

cos1 (cos 2q) =

1
2

2q = q

Hence, LHS = RHS


Solve each of the following for x :
8

15

p
(i) sin1 + sin1 =
2
x
x

(ii) sin1 (x) cos1 (x) = sin1 (3x 2), if x > 0


8

(iii) tan1 (x + 1) + tan1 (x 1) = tan1 31


(iv) tan1 2x + tan1 3x =

www.thinkiit.in

p
4

13
Sol.

INVERSE TRIGONOMETIC
(i)

15

p
sin1 x = sin1 x

2

15
x

p
-1 8
8

= sin 2 - sin x = cos sin -1

15
x

8
= 1-

(ii)

15

p
We have sin1 x + sin1 x =


2

289
x2

225

=1

=1

64
x2

x = 17

But, x = 17 cannot satisfy the given equation.


\
x = 17
1
Let sin x = a and cos1 x = b. Then
x = sin a and x = cos b

cos a = 1- x 2 = sin b
From the given condition, we have
a b = sin1 (3x 2)

3x 2 = sin (a b)
= sin a cos b cos a sin b

3x 2 = x2 (1 x2)

3x 2 = 2x2 1

2x2 3x + 1 = 0
(2x 1) (x 1) = 0

(iii)

x = 1,

1
2

We have, tan1 (x + 1) + tan1 (x 1) = tan1

8
31

( x + 1) + ( x - 1)
8
tan1 1 - ( x + 1)( x - 1) = tan1
31

2x
1 - ( x 2 - 1)

8
,
31

assuming that (x + 1) (x 1) < 1


i.e., x2 1 < 1

2x
2 - x2

8
31

62x = 16 8x2
8x2 + 62x 16 = 0
4x2 + 31x 8 = 0

x=

- 31 961 + 128
8

i.e.,

- 31 33
8

1
4

x2 < 2

or 8

When x = 8, x2 = 64 </ 2. Hence, we reject this value of x. Hence, the required value is x =
(iv)

We have, tan1 2x + tan1 3x =

p
4

www.thinkiit.in

1
.
4

14

INVERSE TRIGONOMETIC

2x + 3 x

p
tan1 1 - (2x ) (3x ) =
4

5x

=1

1 - 6x2

x=

6x2 + 5x 1 = 0

- 5 25 + 24
12

-5 7
12

= 1 or

1
6

Now the formula,


x+y

tan1 x + tan1 y = tan1 1 - xy holds only when xy < 1


Thus, when x = 1, (2x) (3x) = (2) (3) = 6 > 1
So, we reject x = 1 and accept x =
Ex.8

Solve for x : 2 tan1 x = sin1

Sol.

Let a = tan q and b = tan f.


2a

2
1+ a

Then, sin1

1
6

2a
1 - b2
1
2 cos
1+ a
1+ b2

2 tan q

2
1 + tan q

= sin1

= sin1 (sin 2q) = 2q


and

cos

1 - b2

1 + b2

= cos

1 - tan2 f

1 + tan2 f

= cos1 (cos 2f) = 2f


Hence,
RHS = 2q 2f = 2 (q f)
= 2 (tan1 a tan1 b)
So, the given equation implies
2 tan1 x = 2 (tan1 a tan1 b), 1 < a < 1, 1 < b < 1

tan1 x = tan1 a tan1 b


a-b

= tan1 1 + ab ; ab > 1

Ex.9

Sol.

x=

a-b
1 + ab

; ab > 1

Solve :
(i)
2 tan1 (cos x) = tan1 (2 cosec x)
1- x
1+ x

1
2

(ii)

tan1

(iii)
(i)

sin [2 cos1 {cot (2 tan1 x)}] = 0


We have
2 tan1 (cos x) = tan1 (2 cosec x)

tan1 x (x > 0)

2 cos x

2
1 - cos x

tan1

2 cos x
2

1 - cos x

= tan1 sin x

2
sin x

sin x (cos x sin x) = 0


when sin x = 0, x = np, n Z

sin x cos x = 1 cos2 x = sin2 x

sin x = 0 or cos x sin x = 0

www.thinkiit.in

15

INVERSE TRIGONOMETIC
p
4

when cos x sin x = 0 or tan x = 1, x = np +


(ii)

We have, tan1

1
2

tan1 x
1
2

tan1 1 tan1 x =
p
4

(iii)

1- x
1+ x

= tan1 x +

tan1 x =

We have,

2
3

(x > 0)

1
2

tan1 x =

p
4

p
6

1
3

2x

1 - x 2

=0

(Q 2 tan-1 x = tan1


2x

=0

(Q cot1 x = tan1

2x

1- x

sin 2 cos-1
=0

p
6

sin [2 cos {cot (2 tan x)}] = 0


1

1- x
sin 2 cos-1cot cot -1

sin

2x
1- x2

1
)
x

2
1 - x 2
-1 1 - x 2

1sin 2

2 x
2x

1 - x2

1-
2x

=0

(Q 2 cos1 x = sin1 (2x 1- x 2 )]

=0

1- x2
x

= 0

or

(1 x2)2 = 4x2
Now,

1 - x2

tan1 x

x = tan

3
2

(Q tan1 1 + xy = tan1 x tan1y)

sin 2 cos-1cot tan-1

1 - x2

1-
2x

x-y

tan1 x

=0

1 x = 0 or
2

1 - x2

2x

=1

x = 1

(1 x2)2 = 4x2 implies


(1 x2)2 (2x)2 = 0
2
(1 x 2x) (1 x2 + 2x) = 0
1 x2 2x = 0
or
1 x2 + 2x = 0
2
x + 2x 1 = 0
or
x2 2x 1 = 0
x = 1 2

or

x=1 2

Hence, x = 1, 1 2 , 1 2

www.thinkiit.in

or

16

INVERSE TRIGONOMETIC

UNSOLVED PROBLEMS
EXERCISE I
Q.1

Evaluate the following :


(i)

Q.2

4p

cos1 cos 3

(ii)

cos1 (cos 10)

(iii)

Prove that
a-b

b-c

c -a

tan1 1 + ab + tan1 1 + bc + tan1 1 + ca

3
3
a3 - b3
3
3
+ tan1 b - c + tan1 c - a
= tan1
3 3
3 3
3 3

1+ a b

Q.3

12
13

+ cos1

4
5

+ tan1

63
16

=p

Prove that

x
a-b
2 tan1 a + b tan 2 = cos1

Q.5

1+ c a

Prove that
sin1

Q.4

1+ b c

If tan1x + tan1y + tan1z =

b + a cos x

a + b cos x

for 0 < b a and x 0

p
, prove that
2

xy + yz + zx = 1
Q.6

If cos1x + cos1y + cos1z = p, prove that


x2 + y2 + z2 + 2xyz = 1

Q.7

If sin1x + sin1y + sin1z = p, prove that


x 1- x 2 + y 1- y 2 + z 1- z 2 = 2xyz

Q.8

Solve : tan1 2x + tan1 3x =

Q.9

Solve : sin1x + sin1y =

p
4

2p
3

cos1x cos1y =

p
3

Q.10

If sin [2 cos1 {cot (2 tan1 x)}] = 0, find x.

Q.11

If 1 x, y, z 1, such that sin1x + sin1y + sin1z =

3p
2

find the value of


x2000 + y2001 + z2002

9
x

2000

+y

2001

+ z 2002

www.thinkiit.in

tan cos-1
3
2

17
Q.12

INVERSE TRIGONOMETIC
Prove that
tan1

Q.13

1
3

+ ........... + tan1

= tan1 n + 2

n + n +1
2

Sum to n terms the series

.
1
+
1
2
x

tan1

Q.14

1
7

+ tan1

.
1
+
2
3
x

.
1
+
3
4
x

+ tan1

+ tan1

+...........

Establish the algebraic relation between x, y, z if tan1x, tan1y, tan1z are in A.P. and if further x, y, z are
also in A.P., their prove that x = y = z

Q.15

If tan1x + tan1y + tan1z =

Q.16

Solve that equation for x ;


2x

3 sin1

Q.17

and x + y + z = 3 , then prove that x = y = z

4 cos1

1 - x2
1+ x

+ 2tan1

2x
1- x2

p
3

If sin (p cos q) = cos(p sin q), prove that


q=

Q.18

1+ x

p
2

1
2

Prove that tan1

sin1

yz
xr

3
4

zx

+ tan1 yr + tan1

xy
zr

p
,
2

where x2 + y2 + z2 = r2
Q.19

Prove that
a1 x - y

a2 - a1

a3 - a2

an - an-1

tan1 a y + x + tan1 a, a + 1 + tan1 a a + 1 + .......+ tan1 a a + 1 + tan1 a = tan


n
2

n n-1

2 3
x
y

Q.20

If a1, a2, a3, .............. form an A.P. with common difference d (a > 0, d > 0) prove that
d

-a

n+1
n
tan1 1 + a a + tan1 1 + a a + .......... + tan1 1 + a a
= tan1 1 + a a
1 2
2 3
n n+1
1 n+1

www.thinkiit.in

18

INVERSE TRIGONOMETIC

BOARD PROBLES
EXERCISE II
1

Q1.

p
Prove that following : tan1 3 + tan1 5 + tan1 7 + tan1 8 = .




4

Q2.

Using principal value, evaluate the following : cos1 cos 3 + sin1 sin 3

2p

1 + sin x + 1 - sin x
p
x
Prove the following : cos1 1 + sin x - 1 - sin x = , x 0,
2
4

OR
Solve for x : 2 tan1(cos x) = tan1 (2 cosec x)

Q3.

Q4.

Write the principal value of cos1 cos

Q5.

Prove the following : tan1 x + tan1

7p

2x

1 - x2

3x - x 3

2
1- 3x

1 + x2

[CBSE 2010]

2 + x2

4p
.
5

[CBSE 2010 ]

Q6.

Find the value of sin1 sin

Q7.

p
1
Prove that : tan1 1 + x + 1 - x = cos1 x,

4
2

1+ x - 1- x

1
2

x1

6
-1 3
-1 3
Prove the following : cos sin 5 + cot 2 = 5 13

Show that :

Q8.
Q9.

[CBSE 2009]

= tan1

Prove the following : cos [tan1 (sin {cot1 x)}] =

[CBSE 2008]

[CBSE 2009]

OR

2p

[CBSE 2008]

[CBSE 2011]
[C.B.S.E. 2012]

tan 1 sin-1 3 = 4 - 7
2

OR

Solve the following equation :


3
4

cos(tan1x) = sin cot -1

[C.B.S.E. 2013]

ANSWER KEY
EXERICISE 1 (UNSOLVED PROBLEMS)
1. (i)

2p
3

11. 0

3- 5

8. x =

nx

1 + (n + 1)x 2

16. x = 3

(ii) (4p 10) (iii)


1

13. S = tan

1
6

9. x =

1
, y= 1
2

EXERICISE 2 (BOARD PROBLEMS)


Q2. p

Q3.

p
4

Q4.

5p
6

Q6.

p
5

www.thinkiit.in

10. x = 1, (1 2 )